1986
DOI: 10.3109/10826088609074848
|View full text |Cite
|
Sign up to set email alerts
|

Situational Factors Related to Rural Adolescent Alcohol Use

Abstract: Factors and situations associated with alcohol use in a sample of rural junior and senior high school students are examined. Much research has shown that age, gender, grade in school, religiosity, socioeconomic status, and involvement in extracurricular activities are all related to adolescent alcohol use. The present paper looks at the relationship between these factors and situations which might be conducive to drinking (e.g., driving around in a car, before going to a party, etc.) to determine whether the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Not only is the school environment an important social context for young people, but school performance is related to many other life events. Rural-based studies find the same pattern as urban-based studies; that is, there is a clear association between drug use and a lower grade point average (Bloch et al 1991;Wolford and Swisher 1986), lower participation in extracurri-cular activities (Gibbons et al 1986;Wolford and Swisher 1986), and less time spent with homework assignments (Gibbons et al 1986;Wolford and Swisher 1986).…”
mentioning
confidence: 71%
“…Not only is the school environment an important social context for young people, but school performance is related to many other life events. Rural-based studies find the same pattern as urban-based studies; that is, there is a clear association between drug use and a lower grade point average (Bloch et al 1991;Wolford and Swisher 1986), lower participation in extracurri-cular activities (Gibbons et al 1986;Wolford and Swisher 1986), and less time spent with homework assignments (Gibbons et al 1986;Wolford and Swisher 1986).…”
mentioning
confidence: 71%
“…Research suggests that adolescents who attend religious services more frequently are less likely to have problems with substance use. In a study of rural adolescents, Gibbons et al (1986) found that those who attended religious services with greater frequency were less likely to drink alcohol. Zimmerman and Maton (1992) found similar results among urban black youths, with adolescents who more often attended religious services less likely to report alcohol or substance abuse.…”
Section: Religiositymentioning
confidence: 99%
“…With regard to personal characteristics, most studies of adolescent drinking have found that older adolescents are much more likely to report experience with alcohol and have suffered negative consequences associated with greater quantities of alcohol consumed (Hahn, 1982;Boyle & Offord, 1986). Gibbons et al (1986aGibbons et al ( , 1986b; Chambers, Inciardi, and Siegal (1982); Boyle and Offord (1986); Werner (1991); and Dignan et al (1986), all report gender differences in their adolescent studies. They found higher frequencies of alcohol use among males at all ages and greater quantities consumed among their rural male samples.…”
Section: Epidemiology: Risk Factorsmentioning
confidence: 99%
“…Early studies of rural adolescents reported lower rates of alcohol use than urban comparison groups (Napier, Carter, & Pratt, 1981;Gibbons, Wylie, Echterling, & French, 1986a, 1986b. However, more recent national surveys of high school seniors have found few differences in use between rural and urban teens (Johnston, OMalley, & Bachman, 1989).…”
Section: Epidemiology: Prevalencementioning
confidence: 99%